Novel Synthesis of 3-Amino-2-pyrones and 3-Hydroxy-4-pyridones via Double Ring-Opening Reactions of 4-Pyrone Epoxides with Amines - Titova, Polina K.; Alikin, Nikita A.; Kaurova, Alexandrina V.; Viktorova, Viktoria V.; Simbirtseva, Alena E.; Steparuk, Elena V.; Eltsov, Oleg S.; Obydennov, Dmitrii L.; Sosnovskikh, Vyacheslav Y. (Synthesis, 2025)
The general method for the synthesis of 3-amino-2-pyrones based on the domino reaction of 4-pyrone epoxides with amines has been developed. The formation of the products includes selective Michael addition, double ring-opening, and facile deformylation. The nature of amine has a strong effect on the transformation governed by the cyclization of polycarbonyl intermediates. The reaction with aromatic amines is followed by a side dearoylation process to produce dihydropyrroles. The use of ammonium acetate as a nucleophile in DMSO provides a new reaction pathway yielding 3-hydroxy-4-pyridones. Tautomerism of the obtained products has been studied.
Keywords: 4-Pyrone epoxide; 3-Amino-2-pyrone; 3-Hydroxy-4-pyridone; Double ring-opening; Deformylation